Prinsip Kesantunan Berbahasa dalam Lakon Drama Ayahku Pulang Karya Usmar Ismail - Elan Halid (Universitas Ngudi Waluyo, 2021)
The problem to be discussed in this research is how the principle of language politeness in the drama play Ayahku Pulang by Usmar Ismail is reviewed from 6 maxims, namely: the maxim of wisdom, the maxim of generosity, the maxim of appreciation, the maxim of simplicity, the maxim of consensus, and the maxim of sympathy. Ismail describes the struggle of a father who has the heart to leave his wife and young children in pursuit of wealth, so that he forgets his responsibility as a father to his children. speech contains the implied words in it that are interesting to research on the principles of politeness. Language politeness is a matter of showing awareness of the dignity of others in language, both when using spoken language and in written language. The purpose of this research is to describe the principles of language politeness in the drama play Ayahku Pulang karya Usmar Ismail in terms of six maxims. This type of research is qualitative with descriptive methods. The data of this research are utterances in the drama play Ayahku Pulang by Usmar Ismail. The data source in this research is the drama script Ayahku Pulang. the work of Usmar Ismail. From the research data findings, the researcher found 34 data, namely: the maxim of wisdom there are 6 data, the maxim of generosity there are 6 data, the maxim of appreciation has 6 data, the maxim of simplicity has 3 data, the maxim of consensus contains 2 data, and the maxim of sympathy has 11 data. The conclusion of this research is that the maxim that is mostly found is sympathetic maxims.